Assessment of immune interference, antagonism, and diversion following human immunization with biallelic blood-stage malaria viral-vectored vaccines and controlled malaria infection. - Elias, S; Collins, K; Halstead, F; Choudhary, P; Bliss, C; Ewer, K; Sheehy, S; Duncan, C; Biswas, S; Hill, A; Draper, S (2013)
Overcoming antigenic variation is one of the major challenges in the development of an effective vaccine against Plasmodium falciparum, a causative agent of human malaria. Inclusion of multiple Ag variants in subunit vaccine candidates is one strategy that has aimed to overcome this problem for the leading blood-stage malaria vaccine targets, that is, merozoite surface protein 1 (MSP1) and apical membrane Ag 1 (AMA1). However, previous studies, utilizing malaria Ags, have concluded that inclusion of multiple allelic variants, encoding altered peptide ligands, in such a vaccine may be detrimental to both the priming and in vivo restimulation of Ag-experienced T cells. In this study, we analyze the T cell responses to two alleles of MSP1 and AMA1 induced by vaccination of malaria-naive adult volunteers with bivalent viral-vectored vaccine candidates. We show a significant bias to the 3D7/MAD20 allele compared with the Wellcome allele for the 33 kDa region of MSP1, but not for the 19 kDa fragment or the AMA1 Ag. Although this bias could be caused by "immune interference" at priming, the data do not support a significant role for "immune antagonism" during memory T cell restimulation, despite observation of the latter at a minimal epitope level in vitro. A lack of class I HLA epitopes in the Wellcome allele that are recognized by vaccinated volunteers may in fact contribute to the observed bias. We also show that controlled infection with 3D7 strain P. falciparum parasites neither boosts existing 3D7-specific T cell responses nor appears to "immune divert" cellular responses toward the Wellcome allele.